Antifungal activity and action mechanisms of yeasts isolates from citrus against Penicillium italicum - da Cunha, Tatiane [UNESP]; Ferraz, Luriany Pompeo [UNESP]; Wehr, Pitt Paul; Kupper, Katia Cristina [UNESP] (Elsevier, 2018)
Penicillium italicum (Blue mold) is a major postharvest disease of citrus. An alternative to controlling the disease is through the use of yeasts. The purpose of the present study was to screen effective yeast antagonists against P. italicum, isolated from soil, leaves, flowers, and citrus fruits, to assess the action mechanisms of the yeast isolates that were demonstrated to be effective for biocontrol, and to identify the most effective yeast isolates for the biocontrol of blue mold. The in vitro assays showed that six yeast strains inhibited up to 90% of the pathogen's mycelial growth. In vivo assays, evaluating the incidence of blue mold on sweet oranges, the strains ACBL-04, ACBL-05, ACBL-10 and ACBL-11 were effective, demonstrating the potential for the blue mold control when preventively applied, whereas the ACBL-08 strain showed a high potential to preventive and curative applications. Additional studies on the modes of action of these yeast strains showed that most of the evaluated yeast strains did not produce antifungal substances, in sufficient quantities to inhibit the pathogen growth. Competition for nutrients was not a biocontrol strategy used by the yeast strains. The ‘killer’ activity might be the main action mechanism involved in P. italicum biocontrol. This study indicated that the multiple modes of action against the pathogen presented by yeasts may explain why these strains provided P. italicum control under in vitro and in vivo conditions. However, further studies in future might be able to elucidate the ‘killer’ activity and its interaction with pathogen cells and the bioproduct production using Candida stellimalicola strains for control postharvest diseases.
Keywords: Blue mold; Citrus sinensis; Hydrolytic enzymes; Yeast antagonists; ‘Killer’ factor